An enzyme-linked immunosorbent assay (ELISA) for detection of antibodies against Toxocara vitulorum in water buffaloes - Starke-Buzetti, W. A.; Machado, R. Z.; Zocoller-Seno, M. C. (Elsevier B.V., 2001)
Toxocara vitulorum, a parasite of the small intestine of cattle and water buffaloes, is mainly acquired by calves via the colostrum/milk from infected cows. To understand the development of immune responses in calves, antibody levels to a soluble extract antigen (Ex) from T. vitulorum infective larvae were measured by an indirect ELISA with sera of 15 buffalo calves, which were sampled every 15 days for the first 180 days after birth and 9 buffalo cows during the perinatal period. From all serum samples examined during the first 180 days, antibody level was lowest and highest in calves at 1 day of age before and after suckling colostrum, respectively, suggesting that the origin of antibodies was the colostrum. Immediately after birth, antibody levels in suckled calves remained at high levels until day 15, began to decrease to lower levels between 15 and 30 days and remained relatively stable until 120 days. By comparing the immune responses of these animals with their parasitological status it was considered possible to determine if passively acquired or actively produced antibodies provided protection against the infection. High numbers of T. vitulorum eggs in the feces between 30 and 60 days indicated that passively acquired antibodies did not provide protection against the infection, at least during these first days, and the maximum fecal egg counts during 30-45 days were coincident with decreased antibody levels. Between 60 and 120 days, when serum antibodies were detected at reduced, but stable levels, adult nematodes were expelled from the intestines and no more T. vitulorum eggs were found, suggesting development of acquired resistance. However, the potential and functional protective role of the antibodies against T. vitulorum infection and the process of self-cure requires further investigation. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Toxocara vitulorum; water buffalo; ELISA; immune responses